Validation of the Microreader 28A ID System: A 6‐dye multiplex amplification assay for forensic application. Issue 19 (19th August 2021) - Yin, Lu; Zhu, Jing; Qu, Shengqiu; Li, Yifan; Liu, Yuqing; Yu, Zailiang; Yang, Fan; Zhang, Ranran; Xue, Jiaming; Huang, Sicheng; Liang, Weibo
Abstract: The Microreader 28A ID System is a new 28‐plex genotyping system with 6‐dye multiplex amplification, which allows the simultaneous amplification of all 20 Combined DNA Index System (CODIS) core loci (CSF1PO, D3S1358, D5S818, D7S820, D8S1179, D13S317, D16S539, D18S51, D21S11, FGA, TH01, TPOX, vWA, D1S1656, D2S441, D2S1338, D10S1248, D12S391, D19S433, D22S1045), plus five extended STRs loci (D6S1043, Penta D, Penta E, DYS391, SE33), 2 Y‐Indels (Rs2032678, Rs771783753), and the amelogenin loci. This system can be used for forensic analyses, such as personal identification, kinship testing, scientific research, database applications, and other aspects of human genetic identification. The validation of the Microreader 28A ID System followed the "Validation Guidelines for DNA Analysis Methods (2016)" described by the Scientific Working Group on DNA Analysis Methods and the regulations published by the China Ministry of Public Security. Our tests included PCR‐based studies, sensitivity study, precision and accuracy evaluation, stutter percentage and heterozygous peak height ratio, inhibitor tests, species specificity, and population studies. The validation results suggest that the Microreader 28A ID system is a robust and reliable amplification kit for personal identification, kinship testing, and forensic database applications.